Probing Functional Changes in Exocyst Configuration with Monoclonal Antibodies - Inamdar, Shivangi M.; Hsu, Shu-Chan; Yeaman, Charles (Frontiers in Cell and Developmental Biology, 2016)
Spatial regulation of exocytosis relies on the exocyst, a hetero-octameric protein complex that tethers vesicles to fusion sites at the plasma membrane. Nevertheless, our understanding of mechanisms regulating exocyst assembly/disassembly, localization and function are incomplete. Here, we have exploited a panel of anti-Sec6 monoclonal antibodies (mAbs) to probe possible configurational changes accompanying transitions in exocyst function in epithelial MDCK cells. Sec6 is quantitatively associated with Sec8 in high molecular weight complexes, as shown by gel filtration and co-immunoprecipitation studies. We mapped epitopes recognized by more than twenty distinct mAbs to one of six Sec6 segments. Surprisingly, mAbs that bound epitopes in each segment labeled distinct subcellular structures. Antibodies to epitopes in N-terminal domains labeled Sec6 in either cytosolic or nuclear pools, whereas those that bound epitopes in C-terminal domains labeled membrane-associated Sec6. In this latter group, we identified antibodies that labeled distinct Sec6 populations at the apical junctional complex, desmosomes, endoplasmic reticulum and vimentin-type intermediate filaments. That each antibody was specific was verified by both Sec6 RNAi and competition with fusion proteins containing each domain. Comparison of non-polarized and polarized cells revealed that many Sec6 epitopes either redistribute or become concealed during epithelial polarization. Transitions in exocyst configurations may be regulated in part by the actions of Ral GTPases, because the exposure of Sec6 C-terminal domain epitopes at the plasma membrane is significantly reduced upon RalA RNAi. To determine whether spatio-temporal changes in epitope accessibility was correlated with differential stability of interactions between Sec6 and other exocyst subunits, we quantified relative amounts of each subunit that co-immunoprecipitated with Sec6 when antibodies to N-terminal or C-terminal epitopes were used. Antibodies to Sec6NT co-precipitated substantially more Sec5, -10, -15, Exo70 and -84 than did those to Sec6CT. In contrast, antibodies to Sec6CT co-precipitated more Sec3 and Sec8 than did those to Sec6NT. These results are consistent with a model in which exocyst activation during periods of rapid membrane expansion is accompanied by molecular rearrangements within the holocomplex or association with accessory proteins, which expose the Sec6 C-terminal domain when the complex is membrane-bound and conceal it when the complex is cytoplasmic.